Capacity Planning for Vertical Search Engines: An Approach Based on Coloured Petri Nets - Marin-Caihuan, J; Inostrosa-Psijas, A (2012)
This paper proposes a Colored Petri Net model capturing the behaviour of vertical search engines. In such systems a query submitted by a user goes through different stages and can be handled by three different kinds of nodes. The proposed model has a modular design that enables accommodation of alternative/additional search engine components. A performance evaluation study is presented to illustrate the use of the model and it shows that the proposed model is suitable for rapid exploration of different scenarios and determination of feasible search engine configurations. © 2012 Springer-Verlag.